Comparative Evaluation of Intra-articular Ozone and Steroid Treatments in Patients with Coxarthrosis under Ultrasound Guidance: A Retrospective Study - Yilmaz Karaduman; Arzu Muz; Azize Serçe; Servi Yildirim; Ismail Eren Durmus; Suna Akin Takmaz (Journal of Clinical and Diagnostic Research)
Introduction: Osteoarthritis (OA) is the most common degenerative joint disease characterised by the loss of articular cartilage and synovial inflammation. This condition causes stiffness and swelling in the joint, as well as pain, loss of movement and disability. When performed under Ultrasound Guidance (USG), steroid treatments offer several advantages. On the other hand, ozone therapy accelerates anabolic mechanisms, provides vascularisation of cartilage and bone, and slows down the degenerative process. Additionally, it affects inhibitory cytokines, antioxidant enzymes, and neo-angiogenesis. Aim: To evaluate and compare the effectiveness of USG intra-articular ozone therapy versus corticosteroid injections in managing hip OA (coxarthrosis) in patients who have not responded to conventional treatments. Materials and Methods: A retrospective comparative study was conducted at Ankara Training and Research Hospital, Ankara, Altındag, Turkey, from August 2021 to August 2022. Patients unresponsive to conventional treatments were divided into two groups: Group A (n=30) received intra-articular steroid (triamcinolone acetonide), and Group B (n=23) received three weekly ozone sessions (200 μg/20 mL), both under USG. Clinical outcomes were assessed using the Visual Analog Scale (VAS) for pain and the Harris Hip Score (HHS) for functional status, both pre- and post-treatment. Monthly analgesic use was monitored before treatment and at the 1st week, 1st month, 3rd month and 6th month. Statistical analysis were conducted using Unpaired t-tests and Chi-square tests. A p-value <0.05 was considered statistically significant. Results: A total of 53 patients (mean age 63.23±10.50 years) participated in the study. Analgesic needs decreased in both groups, with no significant differences observed in the 1st week, 1st month, 3rd month, and 6th month (p-value=0.139, p-value=0.724, p-value=0.391, p-value=0.546). The most notable improvement occurred one month post-treatment, particularly in low-stage coxarthrosis. Increases in HHS scores and decreases in VAS values for stages 2-3 were statistically significant in both groups (p-value <0.001). Conclusion: The effectiveness of steroid and ozone therapy for coxarthrosis varies by disease stage. Both treatments are more effective in the early stages, while ozone is ineffective and steroids offer limited benefits in advanced stages. Thus, treatment planning should consider the disease stage, and alternative strategies should be explored for advanced cases. Clinicians should prioritise early intervention and seek alternative options for better patient outcomes.